The influence of electronic fiscal devices (EFDS) on value added tax (VAT) collection: A case of VAT registered traders in Morogoro Municipality, Tanzania. - Chamshama, Daffa (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfilment of the requirements for award of Master of Business Administration in Corporate Management (MBA-CM) of Mzumbe University